The trend of occupationl change of currently rural family labor - THỊ LƯUNGỌC (Tạp chí Nghiên cứu Khoa học Công đoàn, 2018)
Morality is a particular concern in the changing society. Indeed moral education in the family at the right time is very necessary. The study shows that perception of ethnic education in rural family nowdays is more concentrated on how to behave properly toelders, to take care for family members, to obey teachers, and to create proper attiudes of behavior between people and people, as well as among villagers. is the proper mothods percieved by rural family are to provide advices and reminds that relevance to psychology of teenage.